Análisis del mercado de bonos en Colombia entre 2019 y primer semestre del 2021 (2021)
In this paper, an analysis of the issuance of bonds in Colombia between 2019 and the first semester of 2021 is developed, in the first instance the issue of the fixed income market is addressed highlighting its main characteristics, in the second place, the entire related topic is developed With the issuance of bonds and the subjects that intervene in the placement process, in third place the types of bonds and the way in which they are negotiated in the national financial market are classified and characterized. In a fourth stage, the data on the issuance of bonds during 2019, 2020 and the first semester of 2021 is addressed, highlighting the main issuing companies during this season, identifying which are the main economic sectors that participate in the issuance of these income securities. fixed. Ultimately, the nation's foreign debt represented inbond issuance and the main foreign debt bondholders are analyzed.